The virgin of Guadalupe and the conversos : uncovering hidden influences from Spain to Mexico - Hernández, Marie Theresa, 1952- (Latinidad., 2014)
Hidden lives, hidden history, and hidden manuscripts. In The Virgin of Guadalupe and the Conversos, Marie-Theresa Hernández unmasks the secret lives of conversos and judaizantes and their likely influence on the Catholic Church in the New World. The terms converso and judaizante are often used for descendants of Spanish Jews (the Sephardi, or Sefarditas as they are sometimes called), who converted under duress to Christianity in the fourteenth and fifteenth centuries. There are few, if any, archival documents that prove the existence of judaizantes after the Spanish expulsion of the Jews in 149.